2021
DOI: 10.15829/1560-4071-2021-4316
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study: carotid endarterectomy in the first hours after ischemic stroke

Abstract: Aim. To analyze inhospital outcomes of carotid endarterectomy (CE) in the acute period (within 3 days from the onset) of ischemic stroke.Material and methods. This retrospective multicenter study for the period from January 2008 to August 2020 included 357 patients who underwent CE in the acute period of stroke. An interdisciplinary commission defined the revascularization timing. There were following inclusion criteria: 1. Mild neurological disorders: NIHSS stroke of 3-8; modified Rankin Scale score <2; Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Albeit current guidelines do not specify the benefits of either ECEA or virtually assisted CCEA [18] , we suggest that cerebral revascularization should become increasingly personalised. Systemic risk factors for the development of restenosis affect CEA outcomes regardless of intervention type [32][33][34][35][36] . Most of them are modifiable, yet it has been shown that genetic background also affects the long-term outcomes [37][38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Albeit current guidelines do not specify the benefits of either ECEA or virtually assisted CCEA [18] , we suggest that cerebral revascularization should become increasingly personalised. Systemic risk factors for the development of restenosis affect CEA outcomes regardless of intervention type [32][33][34][35][36] . Most of them are modifiable, yet it has been shown that genetic background also affects the long-term outcomes [37][38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…При анализе отдаленных результатов КЭЭ у больных с СД 2 авторы приводят данные, доказывающие, что в этой когорте пациентов больше частота развития рестеноза ВСА, ОНМК, ИМ, летального исхода [31][32][33]. Настоящие процессы, безусловно, являются мультитаргетными и включают в себя наследственность, образ жизни, последствия метаболического синдрома [34,35].…”
Section: результатыunclassified
“…In the presence of hemodynamically significant stenosis of the internal carotid artery (ICA), some studies come to conclusions about the safety and efficacy of both carotid endarterectomy and carotid angioplasty with stenting in the acute period (days 1-3) stroke [6] , [7] , [8] , [9] , [10] . Other authors, referring to the high risk of developing hemorrhagic transformation, in some cases call for postponing emergency brain revascularization until the acute (days 4-28) or early recovery (days 29-6 months) stroke periods [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%